2022
DOI: 10.1097/yco.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in the treatment of addictions

Abstract: Purpose of reviewThe purpose of this update is to provide an overview of recent research publications (January 2020--January 2022) on real-time telemedicine solutions for the management of addictions (alcohol, tobacco, opioids, and other drugs). Recent findingsMotivational interviewing by real-time telemedicine showed effectiveness in youth and adults for risky alcohol use and alcohol use disorders, even when a concurrent mental health disorder exists. Live telemedicine is well accepted for managing tobacco us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Telemedicine may be particularly suitable for rural regions. In line with our ndings, vulnerable populations need attention [23], as lack of digital literacy, lack of equipment or lack of privacy may be a barrier for some patients [27,31]. Thus, there is an urgent need to study what treatment modalities (remote vs. in-person) work for whom.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Telemedicine may be particularly suitable for rural regions. In line with our ndings, vulnerable populations need attention [23], as lack of digital literacy, lack of equipment or lack of privacy may be a barrier for some patients [27,31]. Thus, there is an urgent need to study what treatment modalities (remote vs. in-person) work for whom.…”
Section: Discussionmentioning
confidence: 61%
“…Utilization of telemedicine accelerated during the COVID-19 pandemic for many health conditions, including substance use disorders [23,24]. For patients with OUD, telemedicine may improve access to treatment [25], and a recent US cohort study found that its use was associated with improved OAT retention and lower odds of overdose in a during vs. pre-COVID- 19 comparison [26].…”
Section: Discussionmentioning
confidence: 99%
“…Remote addiction treatment and support services can be conven iently provided through telemedicine platforms and mobile health apps. Individuals with addiction can receive medication-assisted treatment, peer support networks, and counsel ling via secure communication channels and virtual consultations [47]. Predictive analytics is another tool that health informatics uses to identify people who may return to use or develop drug-use disorders.…”
Section: Applications Of Health Informatics In Drug Addiction Managementmentioning
confidence: 99%
“…Moreover, if substance use service delivery will become more digitally dependent in the future, it is necessary to anticipate and reconsider the impact of socioeconomic disadvantage and its impact on service access at regional, national, and global levels [ 39 ]. The ongoing digitalization of the substance use sector has thus created a range of specific challenges [ 20 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approaches in the field of substance use include prevention, early intervention, treatment, harm reduction, and recovery. A wide range of emerging digital tools influence these approaches in the domains of research, service provision, and policy making, including apps [16], chatbots [17], algorithms [18], dashboards [19], new service modalities [20][21][22][23], and use of digital tools for substance use [24][25][26][27]. The digitalization of this field brings with it the promise of extended access to services and more efficient distribution of limited expertise by means of telemedicine [28], better public health intelligence concerning substance use trends through data linkage studies [29], predictive models of substance use-related risks through artificial intelligence algorithms [30], improved provision of harm reduction interventions [31,32], and more effective prevention and early interventions for hard-to-reach populations [33,34].…”
Section: Introductionmentioning
confidence: 99%